Case finding for chronic obstructive pulmonary disease in people attending long-term condition clinics in primary care. (November 2016) - Halpin, DMG; Holmes, S; Calvert, J; McInerney, D
Despite increased interest and awareness of chronic obstructive pulmonary disease (COPD), nearly half of the people with COPD remain undiagnosed. Inviting people at risk for screening is unlikely to be effective as many will not attend. Co-morbidities are common in people with COPD but COPD is also a comorbidity of other long-term conditions and people with these conditions are under regular review in primary care clinics. This study aimed to develop a pilot programme to case find people with COPD among patients attending other long-term clinics in primary care. Twenty-three general practices were recruited to participate in South West England. All current or ex-smokers aged ≥35 attending a long-term condition clinic who were not known to have COPD were asked to complete a questionnaire designed to help identify people with COPD and to perform microspirometry. Practices were asked to collect data on up to 100 patients. One thousand three hundred and thirty-three patients were assessed. Four hundred and ten people (31%) were current smokers. Six hundred and thirteen (46%) had high questionnaire scores and 287 (22%) of these also had a forced expiratory volume in 1 second (FEV1 ) below the lower limit of normal (LLN). The mean FEV1 in these patients was 59.0% of predicted (range 22–79.0%). Two hundred and twenty-four had an FEV1 between 50% and 80% of predicted, 50 had an FEV1 between 30% and 50% of predicted. One hundred and sixteen (40%) of the people with an FEV1 below the LLN were still smoking and 55 accepted referral to cessation services. A total of 56% of the other smokers assessed but not thought to have COPD also accepted referral. Assessing symptoms and performing microspirometry in people attending long-term condition clinics in primary care is feasible and has a high yield of identifying people likely to have previously undiagnosed COPD.